2001
DOI: 10.1007/s002340000521
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in N-acetylaspartate/creatine ratio in the motor area and the frontal lobe in amyotrophic lateral sclerosis

Abstract: We studied whether N-acetylaspartate (NAA), a neuronal marker, is reduced in the brain of 14 patients with clinically definite amyotrophic lateral sclerosis (ALS) and whether NAA levels in the motor area and frontal lobe correlate with the clinical features, including frontal lobe function. We also studied 14 normal controls were evaluated. We obtained peak integrals in 1H magnetic resonance spectroscopy (MRS) for NAA, creatine (Cr), and choline-containing compounds (Cho). Severity of the disease was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 0 publications
3
40
0
Order By: Relevance
“…2,[16][17][18][19][20][21] Previous MRSI studies in ALS have demonstrated impaired neuronal integrity in the motor cortex, frontal lobes, and brain stem, with the findings of reduced NAA and NAA normalized to Cr or Cho (NAA/Cr, NAA/Cho). [22][23][24][25] The objective of this study was to assess in vivo neurochemical changes in the MCC and thalamus, 2 regions not previously studied with MRSI but implicated either by pathologic or imaging studies to be in- volved in ALS. Furthermore, the MCC has extensive motor connections and a large number of pyramidal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…2,[16][17][18][19][20][21] Previous MRSI studies in ALS have demonstrated impaired neuronal integrity in the motor cortex, frontal lobes, and brain stem, with the findings of reduced NAA and NAA normalized to Cr or Cho (NAA/Cr, NAA/Cho). [22][23][24][25] The objective of this study was to assess in vivo neurochemical changes in the MCC and thalamus, 2 regions not previously studied with MRSI but implicated either by pathologic or imaging studies to be in- volved in ALS. Furthermore, the MCC has extensive motor connections and a large number of pyramidal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated a reduction in N-acetylaspartate (NAA), a marker of neuronal loss, in patients with ALS compared to controls expressed as absolute concentrations, 11,12 or as ratios of other metabolites like choline (Cho) and creatine (Cr) 10,[13][14][15][16][17][18][19][20][21][22][23][24] in the primary motor cortex, 13,17,19,23,25,26 centrum semiovale, internal capsule, corticospinal tract, cervical spine, 10,12,23 medulla, 5 and brainstem. Whether similar findings might be evident in people at risk for developing ALS, however, remains an unanswered question.…”
mentioning
confidence: 99%
“…In this study, we examine the metabolic and energetic effects of creatine supplementation in human brain using in vivo quantitative 1 H and 31 P spectroscopic imaging. We determine hippocampal measurements of total creatine, N-acetyl aspartate (NAA) and their spectroscopic ratio NAA/Cr.…”
mentioning
confidence: 99%